Diskurs-begrebet i religionshistorisk kontekst - Albinus, Lars (Religionsvidenskabeligt Tidsskrift, 1994)
The aim of the present article is to show how discourses can be seen as the subject matter for the historian of religions, drawing on structuralist and hermeneutic approaches. Despite different positions both approaches point to the topic of discourse as the field of investigation. In this article a discourse is understood as a ramework defining the conditions and possibilities of the creation of meaning within the confines of a communicative group. these religious groups, and their concomitant religious discourses, demarcate themselves vis-a-vis one another by referring to a transcendent reality, each through a specific representative. In ancient Greece, for example, Homer and Orpheus, the inspired poets, count as authorities of two different discourses, the source material of which is available in the text groups presented in the names of these poets. The task is to account for the process of transformation as the outcome of different interacting discourses and the continuous reinterpretation within each. Hence, the paradigmatic shift from mythos to logos is to be seen from this angle and not in the perspective if different mentalities. The analysis of discourse is directed toward the historic situation and the texts themselves, not towards types of imagination defined a priori.